以下程序的输出结果是: a = [“a”,“b”,“c”] b = a[::-1] print(b)
[‘c’, ‘b’, ‘a’]
举一反三
- 10334.以下程序的输出结果是______。 a=[3,2,1] b=a[:] print(b)
- 下列程序段的输出结果是 a = [1,2,3,4,5] b = a c = a[:] b[1] = 6 c[2] = 5 print(a[0]+a[1]+a[2])
- 以下程序的输出结果是: frame = [[1,2,3],[4,5,6],[7,8,9]] rgb = frame[::-1] print(rgb)
- 已知a=[[1,2,3],[2,2],[3,2,1]],则a[1][1]+a[-1][-1]结果是 A: 1 B: 2 C: 3 D: 4
- 下列程序的输出结果是( )。a=[60,70,80]b=ab[1]=90print(a[1])
内容
- 0
以下程序的输出结果是: ls=[[1,2], 'python', [[3,4,'A'],5],[0,7]] print(ls[2][1]) A: 'A' B: p C: 3 D: 5
- 1
10334.以下程序的输出结果是______。 a=[3,2,1] b=a[:] print(b) A: [3,2,1] B: [] C: [1,2,3] D: 0xA1F8
- 2
以下程序的输出结果是( )。a = ["a","b","c"]b = a[::-1]print(b) A: ['b','c', 'a'] B: ["a","b","c"] C: ['b','a','c'] D: ['c', 'b', 'a']
- 3
以下程序的输出结果是()。a=[“a”,“b”,“c”]b=a[::-1]print(b) A: [‘a’,‘b’,‘c’] B: ‘c’,‘b’,‘a’ C: ‘a’,‘b’,‘c’ D: [‘c’,‘b’,‘a’]
- 4
以下程序的输出结果是( )。a = ["a","b","c"]b = a[::-1]print(b) A: ['b','c', 'a'] B: ["a","b","c"] C: ['b','a','c'] D: ['c', 'b', 'a']